Dampak Penambangan Batubara Terhadap Lingkungan dan Ekonomi Masyarakat Batu Kajang Kecamatan Batu Sopang Kabupaten Paser Kalimantan Timur - Ulfa, Shofia; Ali Wardhana (PPJP ULM, 2024)
This study aims to determine the impact of coal mining on the economic environment and society of Batu Kajang, Paser Regency. The unit of analysis in this study is the economy of the people living in the vicinity of coal mining. The method of analyzing qualitative data is actively or continuously until the data is saturated (Miles and Huberman). The results of this study indicate that the impact of coal mining on the environment has a negative impact because it can pollute the environment and decrease water and air quality. On the other hand, the impact of coal mining on the economy of the Batu Kajang community is positive because it is able to lift the local economy with the arrival of mining workers living in Batu Kajang.